2008
DOI: 10.1590/s0100-40422008000400030
|View full text |Cite
|
Sign up to set email alerts
|

Determination of moisture content and water activity in algae and fish by thermoanalytical techniques

Abstract: Recebido em 18/12/07; aceito em 25/2/08; publicado na web em 2/4/09The water content in seafoods is very important since it affects their sensorial quality, microbiological stability, physical characteristics and shelf life. In this study, thermoanalytical techniques were employed to develop a simple and accurate method to determine water content (moisture) by thermogravimetry (TG) and water activity from moisture content values and freezing point depression using differential scanning calorimetry (DSC). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 11 publications
2
26
1
4
Order By: Relevance
“…Fish has the potential to be considered as a balanced food and can therefore be expected to provide relief from malnutrition (Ogundiran, Adewoye, Ayandiran, & Dahunsi, 2014). It also has a high economic value for many countries because it represents the largest share among agribusiness products on the global market (Silva, Silva, Andradel, Veloso, & Santos, 2008). Rahji and Bada (2010) reported that while Nigeria requires about 1.5 million tonnes of fish annually and is expected to meet FAO's recommended minimum fish consumption rate of 12.5 kilograms per head yearly to satisfy basic protein needs, the nation currently imports up to 400,000 tonnes to bridge the fish supply-demand gap.…”
Section: Introductionmentioning
confidence: 99%
“…Fish has the potential to be considered as a balanced food and can therefore be expected to provide relief from malnutrition (Ogundiran, Adewoye, Ayandiran, & Dahunsi, 2014). It also has a high economic value for many countries because it represents the largest share among agribusiness products on the global market (Silva, Silva, Andradel, Veloso, & Santos, 2008). Rahji and Bada (2010) reported that while Nigeria requires about 1.5 million tonnes of fish annually and is expected to meet FAO's recommended minimum fish consumption rate of 12.5 kilograms per head yearly to satisfy basic protein needs, the nation currently imports up to 400,000 tonnes to bridge the fish supply-demand gap.…”
Section: Introductionmentioning
confidence: 99%
“…A further increase in temperature resulted in the decomposition of algal biomass above 450°C, similar trends were reported by da Silva et al . . The other application of TGA is the determination of the ash content of the biomass samples.…”
Section: Resultsmentioning
confidence: 99%
“…Содержание влаги в талломах всех исследованных видов составляло более 70%, что соответствует литературным данным (Murata, Nakazoe, 2001;da Silva et al, 2008;Bruton et al, 2009) (рис. 1).…”
Section: содержание влагиunclassified
“…1). Специфические уровни влажности водорослей изученных родов были аналогичны уровням влажности, описанным в литературе (da Silva et al, 2008), за исключением рода Sargassum, изученный нами представитель которого (S. tenerrimum), имел более высокие значения этого показателя. Самое высокое содержание влаги было в талломах C. scalpelliformis (87,56%), а наиболее низкое -у U. lactuca (78,27%).…”
Section: содержание влагиunclassified
See 1 more Smart Citation